Stultifera navis. Autonomia i emancypacja a dyskurs biologizujący niepełnosprawność - Grabizna, Adrianna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this work I will evoke some ways of illustrating the liminal situation of people with disabilities. I will also refer to the thesis according to which biologizing narrative implicitly conveys a belief that the worse functioning of people with disabilities depends entirely from their "objective", biological functioning which one must come to terms and can at best feel sorry for a person who therefore has limited access to certain human rights (to education, to social, family and sexual life, to work, etc.). I will make a brief philosophical counterpoint to this belief in favour of the thesis that the quality of life of people with disabilities is not directly proportional to the degree of existing biological difficulties. I will also show that the opposite of autonomy is not dependence, but heteronomy, and its example is ableism, just as emancipation is an expression of autonomy.
Keywords: niepełnosprawność; liminalność; autonomia; heteronomia; ableizm; emancypacja; disability; liminality; autonomy; heteronomy; ableism; emancipation